AI as Part of the Pedagogy: A Restorative Justice Approach - Pawlychka, Colleen (Canadian Perspectives on Academic Integrity, 2023)
Concerns around academic integrity (AI) are a national and international focus, as academic misconduct incidents have increased in recent years. Most institutions have committees, departments and policies dedicated to addressing AI, and increasingly recognize the punitive approach as ineffective and counter-productive. Accordingly, many institutions have transitioned from a punitive and reactive approach to an educational and preventative approach, and various faculty members struggle to develop strategies supporting this approach. Restorative justice provides a strong foundation and framework for this transition. Dr. Pawlychka will outline the restorative justice philosophy and share innovative and practical strategies for faculty to use in the classroom to increase student responsibility and capacity for AI while strengthening the faculty-student relationship. Her approach to fostering a culture of academic integrity begins at course and curricula development and continues through all aspects of course delivery, in-class discussion, and instructor-student contact. She will share pedagogical methods, based on RJ philosophy, current research, professional experience, and student feedback, that have resulted in decreased academic misconduct incidents, strengthened student commitment to academic integrity, and enhanced enjoyment of both teaching and learning! Strategies presented will include tips for in-class AI discussion, redefining terminology, development of AI handouts and assignments, and restorative approaches when meeting with students. Participants are invited to bring ‘scenarios’ for discussion.